Perancangan Aplikasi Absensi Karyawan Berbasis Web dengan QR Code sebagai Alat Identifikasi pada PT Konsultan Pajak Barli dan Rekan - Bintang Hartawan Nugraha; Azis Suhendra; Saeful Hasim; Iwan Giri Waluyo (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
Web-based employee attendance application with QR Code as an identification tool is an efficient and practical solution for PT Konsultan Pajak Barli and Rekan in managing employee attendance. In this journal, we describe the design and implementation of the application, as well as discuss the expected benefits from using this application. The methods used in developing this application are requirement analysis, system design, implementation, and testing. The result is an employee attendance application that utilizes QR Code technology to accurately identify employees and efficiently manage attendance data.